Pendekar Muda: The Malay Patriotism-based Mobile Game using Unity - Mokhsin, Mudiana; Zainol, Amer Shakir; Som, Mohd Husni Mohd; Ahmad, Nurul Atikah; Hom , Siti Nordianah Hai; Rosli , Nor Azlin (International Journal of Psychosocial Rehabilitation, 2020)
Patriotism is the spirit of love towards one’s country. A sense of Patriotism is not present by itself in human life, but this feeling has to be fertilized and nurtured to be powerful in the soul of each and every citizen. Patriotism have five elements which is Iconoclastic Patriotism, Symbolic Patriotism, Capitalistic Patriotism, Instinctive Environmental Patriotism and Nationalistic Symbolic Patriotism. The young generations, that born after Malaysia gained independence from Britain in 1957 are the ones who will be leading the government as well as the country in the future. In this modern era, they found to have low spirit of Patriotism. They lack the awareness how important to have Patriotism spirit for the future. In addition, the negative attitude among the young generation could affect the quality of the young generation which can give big impact to the country. Next, lack of the history knowledge because they lost their interest in learning history by using book. The best way to attract their interest to learn history is by converting the information into interactive learning method. The approach that are taken for this project is by giving them awareness about their level of patriotism and also by converting the information into interactive learning method. The objective of this project is to identify the requirements, design and develop Pendekar Muda game of mobile learning application about the Patriotism The paper aims are to develop a game that will show the level of Patriotism and also to give awareness about the Patriotism among the adolescent. The target user for this project are the young generation from the age of 10 to 12 years old that categorized as adolescent. The methodology approach that would apply in this project is Design Thinking model that covered empathies, define, ideate, prototype and testing phase. This methodology is suitable for interactive learning development process. The adolescent can know their level after they answer multiple-choice question. If they cannot achieve the minimum score, there is a help for them to pass the checkpoint. The help consist of information that related to the question. The last part is they can know their result based on their correct answer and the result will display in a graphical way. Last but not least, this application is to improve the spirit patriotism of the young generation.